2006
DOI: 10.1369/jhc.5a6770.2006
|View full text |Cite
|
Sign up to set email alerts
|

Histidine Decarboxylase, DOPA Decarboxylase, and Vesicular Monoamine Transporter 2 Expression in Neuroendocrine Tumors: Immunohistochemical Study and Gene Expression Analysis

Abstract: (GP) S U M M A R Y Histidine decarboxylase (HDC) and vesicular monoamine transporter 2 (v-MAT2) are involved in the biosynthesis and storage of histamine. DOPA decarboxylase (DDC) is involved in the biosynthesis of a variety of amines and shares a high degree of homology with HDC. HDC and v-MAT2 immunoreactivities (IR) have recently been detected in well-differentiated neuroendocrine tumors (WDNETs) and poorly differentiated neuroendocrine carcinomas (PDNECs) of various sites and have been proposed as gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
39
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 28 publications
3
39
0
5
Order By: Relevance
“…This finding indicates that the intracellular decarboxylation process in RIN-5mF cells was not considerably affected by the pharmacologic inhibition by carbidopa. The upregulation of AADC activity in NET cells supports this finding (10,17).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This finding indicates that the intracellular decarboxylation process in RIN-5mF cells was not considerably affected by the pharmacologic inhibition by carbidopa. The upregulation of AADC activity in NET cells supports this finding (10,17).…”
Section: Discussionsupporting
confidence: 75%
“…However, no final consensus about the usefulness of carbidopa premedication before 18 F-FDOPA PET in patients with hyperinsulinemic hypoglycemia has been reached because of the potential reduction of tumoral uptake intensity (9). The risk of 18 F-FDOPA PET false-negative results could be high for tumors with low intracellular AADC activity (10), which are potentially more sensitive to the inhibitory effect of carbidopa.…”
mentioning
confidence: 99%
“…At our Department, in patients with HH and suspected insulinoma, 18 F-FDOPA-PET/CT with contrast enhancement, early acquisition time, and no carbidopa-premedication was performed. In the present study, we evaluated the clinical usefulness of 18 F-FDOPA-PET/CT with the abovementioned conditions that would make this method a 'onestop' examination.…”
mentioning
confidence: 99%
“…In the present study, we evaluated the clinical usefulness of 18 F-FDOPA-PET/CT with the abovementioned conditions that would make this method a 'onestop' examination.…”
mentioning
confidence: 99%
“…High DDC mRNA expression has been noticed in small-cell lung carcinoma (SCLC), neuroblastoma, and pheochromocytoma (Jensen et al, 1990;Gilbert et al, 1999;Uccella et al, 2006). Moreover, it has been suggested that DDC mRNA levels could be a potential biomarker for the detection of minimal residual disease in patients with neuroblastoma and for the discrimination of neuroblastoma from other small round-cell tumours of childhood (Gilbert et al, 1999;Bozzi et al, 2004).…”
mentioning
confidence: 99%